IDNLearn.com makes it easy to get reliable answers from experts and enthusiasts alike. Discover in-depth answers to your questions from our community of experienced professionals.
Sagot :
To determine which of the given options is equivalent to [tex]\( |-12 + 3| \)[/tex], let's analyze each option step-by-step.
First, we calculate the value of [tex]\( |-12 + 3| \)[/tex]:
[tex]\[ -12 + 3 = -9 \][/tex]
Taking the absolute value:
[tex]\[ |-9| = 9 \][/tex]
So, [tex]\( |-12 + 3| = 9 \)[/tex].
Next, we evaluate each provided option separately.
### Option 1: [tex]\(-|12| + |3|\)[/tex]
[tex]\[ |12| = 12 \][/tex]
[tex]\[ |3| = 3 \][/tex]
[tex]\[ -|12| + |3| = -12 + 3 = -9 \][/tex]
### Option 2: [tex]\(-|12| - |3|\)[/tex]
[tex]\[ |12| = 12 \][/tex]
[tex]\[ |3| = 3 \][/tex]
[tex]\[ -|12| - |3| = -12 - 3 = -15 \][/tex]
### Option 3: [tex]\(|12| - |3|\)[/tex]
[tex]\[ |12| = 12 \][/tex]
[tex]\[ |3| = 3 \][/tex]
[tex]\[ |12| - |3| = 12 - 3 = 9 \][/tex]
### Option 4: [tex]\(|12| + |3|\)[/tex]
[tex]\[ |12| = 12 \][/tex]
[tex]\[ |3| = 3 \][/tex]
[tex]\[ |12| + |3| = 12 + 3 = 15 \][/tex]
We compare the results:
- [tex]\(-|12| + |3| = -9\)[/tex]
- [tex]\(-|12| - |3| = -15\)[/tex]
- [tex]\(|12| - |3| = 9\)[/tex]
- [tex]\(|12| + |3| = 15\)[/tex]
The calculation for [tex]\(|12| - |3| = 9\)[/tex] matches the value of [tex]\( |-12 + 3| = 9 \)[/tex].
Therefore, the equivalent expression to [tex]\( |-12 + 3| \)[/tex] is [tex]\(|12| - |3|\)[/tex].
First, we calculate the value of [tex]\( |-12 + 3| \)[/tex]:
[tex]\[ -12 + 3 = -9 \][/tex]
Taking the absolute value:
[tex]\[ |-9| = 9 \][/tex]
So, [tex]\( |-12 + 3| = 9 \)[/tex].
Next, we evaluate each provided option separately.
### Option 1: [tex]\(-|12| + |3|\)[/tex]
[tex]\[ |12| = 12 \][/tex]
[tex]\[ |3| = 3 \][/tex]
[tex]\[ -|12| + |3| = -12 + 3 = -9 \][/tex]
### Option 2: [tex]\(-|12| - |3|\)[/tex]
[tex]\[ |12| = 12 \][/tex]
[tex]\[ |3| = 3 \][/tex]
[tex]\[ -|12| - |3| = -12 - 3 = -15 \][/tex]
### Option 3: [tex]\(|12| - |3|\)[/tex]
[tex]\[ |12| = 12 \][/tex]
[tex]\[ |3| = 3 \][/tex]
[tex]\[ |12| - |3| = 12 - 3 = 9 \][/tex]
### Option 4: [tex]\(|12| + |3|\)[/tex]
[tex]\[ |12| = 12 \][/tex]
[tex]\[ |3| = 3 \][/tex]
[tex]\[ |12| + |3| = 12 + 3 = 15 \][/tex]
We compare the results:
- [tex]\(-|12| + |3| = -9\)[/tex]
- [tex]\(-|12| - |3| = -15\)[/tex]
- [tex]\(|12| - |3| = 9\)[/tex]
- [tex]\(|12| + |3| = 15\)[/tex]
The calculation for [tex]\(|12| - |3| = 9\)[/tex] matches the value of [tex]\( |-12 + 3| = 9 \)[/tex].
Therefore, the equivalent expression to [tex]\( |-12 + 3| \)[/tex] is [tex]\(|12| - |3|\)[/tex].
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Thank you for choosing IDNLearn.com. We’re here to provide reliable answers, so please visit us again for more solutions.